OuterTuning: how are database tuning suggestions in LLMs? - Massena, Lucas Ferraz; Almeida, Ana Carolina (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais Estendidos do XLI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd_estendido.2026.249615, 2026)
Large Language Models (LLMs) have established themselves as promising tools for supporting database tuning. This work extends OuterTuning to incorporate LLMs, providing additional tuning suggestions for the DBA. These suggestions are accompanied by explanations provided by the LLMs themselves. Through experimental scenarios using the TPC-H benchmark, it is verified that LLMs are beneficial, but still have room for improvement.